New surgical technique for pediatric en‐bloc kidney and pancreas transplantation: the pancreas piggy‐back. (16th October 2012) - Waldner, Matthias; Bächler, Thomas; Schadde, Erik; Schiesser, Marc; Immer, Franz; Clavien, Pierre‐Alain; Brockmann, Jens Gunther
Summary Combined pancreas and kidney transplantation is the therapy of choice for type I diabetes patients with associated end‐stage renal disease. To counterbalance increasing waiting lists, there is a clear need to extend the organ donor pool. Although results following simultaneous pancreas and kidney transplantation (SPK) using pediatric organs are encouraging, there is still reluctance in accepting them. This reflects the fear of graft thrombosis and graft failure because of small vessels and little absolute islet cell mass. Simpler transplant techniques for pediatric SPK might lower this threshold. In this article, a novel technique using a "piggy‐back" implantation of the pancreas onto the conduits of en‐bloc grafted kidneys, performed in two consecutive cases, is presented. This technique is associated with less vascular manipulation, requiring only one arterial anastomosis onto the frequently arteriosclerotic arteries of the recipient for all three organs. One‐year follow‐up (14 and 12 months) proved excellent graft function of kidneys and pancreas.